Online Control of Prehension Predicts Performance on a Standardized Motor Assessment Test in 8- to 12-Year-Old Children - Blanchard, Caroline C. V.; McGlashan, Hannah L.; French, Blandine; Sperring, Rachel J.; Petrocochino, Bianca; Holmes, Nicholas P. (Frontiers in Psychology, 2017)
Goal-directed hand movements are guided by sensory information and may be adjusted 'online', during the movement. If the target of a movement unexpectedly changes position, trajectory corrections can be initiated in as little as 100ms in adults. This rapid visual online control is impaired in children with developmental coordination disorder (DCD), and potentially in other neurodevelopmental conditions. We investigated the visual control of hand movements in children in a 'centre-out' double-step reaching and grasping task, and examined how parameters of this visuomotor control co-vary with performance on standardised motor tests often used with typically and atypically developing children. Two groups of children aged 8-12 years were asked to reach and grasp an illuminated central ball on a vertically oriented board. On a proportion of trials, and at movement onset, the illumination switched unpredictably to one of four other balls in a centre-out configuration (left, right, up, or down). When the target moved, all but one of the children were able to correct their movements before reaching the initial target, at least on some trials, but the latencies to initiate these corrections were longer than those typically reported in the adult literature, ranging from 211 to 581 ms. These later corrections may be due to less developed motor skills in children, or to the increased cognitive and biomechanical complexity of switching movements in four directions. In the first group (n=187), reaching and grasping parameters significantly predicted standardised movement scores on the MABC-2, most strongly for the aiming and catching component. In the second group (n=85), these same parameters did not significantly predict scores on the DCDQ-07 parent questionnaire. Our reaching and grasping task provides a sensitive and continuous measure of movement skill that predicts scores on standardized movement tasks used to screen for DCD.